Prosperity Through Sexuality: A study of Outdoor Sexual intercourse as a Ritual in Kemukus Mountain Sragen Central Java - Agus Wahyudi (Journal of Islamic Civilization, 2019)
This research was conducted to find out how the actors interpret the ‘Ngalap Berkah’ execution of ritual sexual intercourse on Mount Kemungkus, as well as what their expectations of the ritual. This research is descriptive research using qualitative methods. Symbolic interaction theory of the main shaft into Helbert Blummer in this study. The results of this research show that the perpetrators ‘Ngalap Berkah’ know of any sexual relationship during the ritual.  They assume that by performing these sexual relationships, their wishes can be easily reached. The results obtained after performing the ritual of the ‘Ngalap Berkah’ can be either a business or work more smoothly, though on the other hand there are also yet to get the results of the ritual.